A review of dissolved gas analysis measurement and interpretation techniques - Abu Bakar, Norazhar; Abu-Siada, Ahmed; Islam, Syed (Institute of Electrical and Electronics Engineers, 2014)
Dissolved gas analysis (DGA) is used to assess the condition of power transformers. It uses the concentrations of various gases dissolved in the transformer oil due to decomposition of the oil and paper insulation. DGA has gained worldwide acceptance as a method for the detection of incipient faults in transformers.